Kērūru Vāsudēvācārya samagra - Vāsudēvācārya, Kerūra,Kalaburgi, Eṃ. Eṃ.,Bidarakundi, Śyāmasundara (Manōhara Grantha Mālā)
Collection of complete short stories, novels and plays of the Kannada author
In Kannada
Keywords: Short stories; Kannada; Kannada drama; Kannada fiction